Les oléagineux en 12000 pages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Oléagineux — 1972 - 1994 Cirad, Montpellier, France, 2001 CD-ROM